UHPLC-MS/MS Analysis of Cannabidiol and Its Metabolites in Serum of Patients with Resistant Epilepsy Treated with CBD Formulations - Malaca, Sara (Pharmaceuticals (Basel), 2021)
Cannabidiol (CBD) is a promising therapeutic agent with analgesic, myorelaxant, and anti-epileptic actions. Recently, a purified form of CBD (Epidiolex(®)) has been approved by the European Medicines Agency (EMA) for the treatment of two highly-refractory childhood-onset epilepsies (Dravet and Lennox-Gastaut syndrome). Given the interindividual response and the relationship between the dose administered and CBD blood levels, therapeutic drug monitoring (TDM) is a valuable support in the clinical management of patients. We herein report for the first time a newly developed and validated method using ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC–MS/MS) to evaluate CBD and its metabolites (i.e., cannabidiol-7-oic acid (7-COOH-CBD), 7-hydroxycannabidiol (7-OH-CBD), 6-α-hydroxycannabidiol (6-α–OH–CBD) and 6-β-hydroxycannabidiol (6-β–OH–CBD)) in serum samples. The method reached the sensitivity needed to detect minimal amounts of analytes under investigation with limits of quantification ranging from 0.5 to 20 ng/mL. The validation results indicated in this method were accurate (average inter/intra-day error, <15%), precise (inter/intra-day imprecision, <15%), and fast (8 min run time). The method resulted to be linear in the range of 1–10,000 ng/mL for CBD-COOH, 1–500 ng/mL for 7-OH-CBD and CBD and 1–25 ng/mL for 6-α–OH–CBD and 6-β–OH–CBD. Serum levels of CBD (88.20–396.31 and 13.19–170.63 ng/mL) as well as of 7-OH-CBD (27.11–313.63 and 14.01–77.52 ng/mL) and 7-COOH-CBD (380.32–10,112.23 and 300.57–2851.82 ng/mL) were significantly higher (p < 0.05) in patients treated with GW pharma CBD compared to those of patients treated with galenic preparations. 6-α–OH–CBD and 6-β–OH–CBD were detected in the first group and were undetectable in the second group. 7-COOH-CBD was confirmed as the most abundant metabolite in serum (5–10 fold higher than CBD) followed by 7-OH-CBD. A significant correlation (p < 0.05) between the dose administrated and a higher bioavailability was confirmed in patients treated with a GW pharma CBD preparation.